O028 Effectiveness of digital brief behavioural therapy for insomnia with wearable technology: pilot randomized controlled trial. (7th October 2021) - Gordon, C; Aji, M; Glozier, N; Bartlett, D; Calvo, R; Marshall, N; Grunstein, R
Abstract: Objective: This pilot trial aimed to test the effectiveness of integration of a wearable device with digital brief behavioural therapy for insomnia (dBBTi) on insomnia symptom severity, sleep metrics and therapy engagement. Participants and Methods: One hundred and twenty-eight participants with insomnia symptoms were randomised to a 3-week dBBTi program with a wearable device enabling sleep data synchronization (dBBTi+wearable group; n = 62) or dBBTi alone (n = 66). We assessed the Insomnia Severity Index (ISI) and modified Pittsburgh Sleep Quality Index (PSQI; wake-after-sleep-onset (WASO), sleep-onset-latency (SOL), and total sleep time (TST)) at baseline and weeks 1, 2, 3, 6 and 12. Engagement was measured by the number of daily sleep diaries. Results: There was no significant difference in ISI scores between the groups (d = 0.7, p = 0.061). The dBBTi+wearable group showed greater improvements in WASO (d = 0.8, p = 0.005) and TST (d = 0.3, p = 0.049) compared to the dBBTi group after 6 weeks. There was significantly greater engagement in the dBBTi+wearable group compared to the dBTi group (d =0.7, p = 0.010). Conclusions: This pilot trial found that wearable device integration with a digital insomnia therapy led to improvements in WASO and TST and enhanced user engagement. We suggest that incorporation of adjunctive wearable technologies may improve digital insomnia therapy.